2019
DOI: 10.1083/jcb.201903006
|View full text |Cite
|
Sign up to set email alerts
|

TFEB controls retromer expression in response to nutrient availability

Abstract: Endosomal recycling maintains the cell surface abundance of nutrient transporters for nutrient uptake, but how the cell integrates nutrient availability with recycling is less well understood. Here, in studying the recycling of human glutamine transporters ASCT2 (SLC1A5), LAT1 (SLC7A5), SNAT1 (SLC38A1), and SNAT2 (SLC38A2), we establish that following amino acid restriction, the adaptive delivery of SNAT2 to the cell surface relies on retromer, a master conductor of endosomal recycling. Upon complete amino aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 48 publications
3
25
0
Order By: Relevance
“…26 Recent work in Hela cells has shown that SLC38A2's adaptive response to nutrient starvation requires retromer-mediated endosomal sorting, which prevents SLC38A2 being sequestered in LAMP1-positive lysosomes. 27 Considering the heterogeneity of response to the stresses, here we assessed the route of SLC38A2 degradation by treating MCF7, MDA-MB-231 and HCC1806 with Bafilomycin A1, a pharmacological inhibitor of autophagosome-lysosome fusion. 28 The levels of SLC38A2 increased consistently after Bafilomycin A1 treatment in all cell lines, suggesting lysosome-mediated degradation of SLC38A2 was also important in these breast cancer cell lines (Fig.…”
Section: Slc38a2 Mrna Is Highly Expressed In Breast Cancer Cell Linesmentioning
confidence: 99%
“…26 Recent work in Hela cells has shown that SLC38A2's adaptive response to nutrient starvation requires retromer-mediated endosomal sorting, which prevents SLC38A2 being sequestered in LAMP1-positive lysosomes. 27 Considering the heterogeneity of response to the stresses, here we assessed the route of SLC38A2 degradation by treating MCF7, MDA-MB-231 and HCC1806 with Bafilomycin A1, a pharmacological inhibitor of autophagosome-lysosome fusion. 28 The levels of SLC38A2 increased consistently after Bafilomycin A1 treatment in all cell lines, suggesting lysosome-mediated degradation of SLC38A2 was also important in these breast cancer cell lines (Fig.…”
Section: Slc38a2 Mrna Is Highly Expressed In Breast Cancer Cell Linesmentioning
confidence: 99%
“…In the absence of retromer, RAB7 loses its dynamic organisation on endosomes and lysosomes and becomes hyperactivated and immobile on lysosomes ( Jimenez-Orgaz et al, 2018 ; Seaman et al, 2018 ). This leads to impaired mTORC1 activity and the induction of autophagy, and the appearance of swollen and evenly dispersed lysosomes ( Jimenez-Orgaz et al, 2018 ; Cui et al, 2019 ; Curnock et al, 2019 ; Kvainickas et al, 2019 ). Moreover, retromer-knockout cells display activation of the TFEB transcription factors ( Curnock et al, 2019 ), master regulators of cellular nutrient sensing and energy metabolism ( Sardiello et al, 2009 ; Settembre et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…This leads to impaired mTORC1 activity and the induction of autophagy, and the appearance of swollen and evenly dispersed lysosomes ( Jimenez-Orgaz et al, 2018 ; Cui et al, 2019 ; Curnock et al, 2019 ; Kvainickas et al, 2019 ). Moreover, retromer-knockout cells display activation of the TFEB transcription factors ( Curnock et al, 2019 ), master regulators of cellular nutrient sensing and energy metabolism ( Sardiello et al, 2009 ; Settembre et al, 2011 ). Thus, besides its role in cargo retrieval and recycling within the endosomal pathway ( Steinberg et al, 2013 ), retromer has emerged as a master regulator of RAB7 in nutrient sensing and signalling ( Jimenez-Orgaz et al, 2018 ; Curnock et al, 2019 ; Kvainickas et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was shown that the promoter regions of Vps35 and Vps26 have response elements for transcription factor EB (TFEB), a master regulator of lysosome biogenesis and autophagy (Sardiello et al, 2009). Upon nutrient deficiency, autophagy is induced and the expression of Vps35 and Vps26 are upregulated (Curnock, Calcagni, Ballabio, & Cullen, 2019). Another study showed that the pharmacological chaperone R55 stabilizes the retromer complex and diminishes the toxicity of Aß oligomers (Mecozzi et al, 2014) in the Drosophila animal model and in mouse hippocampal neurons.…”
Section: The Structure Of the Retromermentioning
confidence: 99%